Electrohydrodynamic and shear-stress interfacial instability of two streaming viscous liquid inside a microchannel for tangential electric fields - Haiwang, Li. (2013)
The electrohydrodynamic and stress instability of the interface between two viscous fluids with different electrical properties under tangential electric fields in a microchannel is analytically and experimentally investigated. In the analytical model, the two-layer system is subjected to a tangential electric field. There is no assumption on the magnitude of the ratio of fluid to electric time scales, and thus the linear Poisson-Boltzmann equation are solved using separation of variable method for densities of bulk charge and surface charge; the electric field and fluid dynamic are coupled only at the interface through the stress balance equations. Under constant flowrates, the fractions of the fluids are calculated for different parameters. Using the calculated fractions, the stability of the system can be determined according to the linear perturbation theory. In the experiments, two immiscible fluids, aqueous NaHCO3 (conducting fluid) and silicone oil (non-conducting fluid) are pumped into a PMMA microchannel. The tangential electric field is added to the aqueous NaHCO3 using a high voltage power supply. The results are recorded using a CCD camera. The results show that the electric field can have either destabilizing or stabilizing effect depending on the ratios of viscosity of the two fluids. The flowrates, zeta potential, and dimension of the microchannel affect the growth rate of the perturbation. Both experimental and analytical results show a good agreement.